Unearthing the International Financial Reporting Standards (IFRS) in the Accounting Curriculum in Saudi Arabia - An Empirical Study - Alfify, Mohammed; Faiyyaz, Abdul Ghani; Malik, Abdullah (International Journal of Accounting and Financial Reporting, 2021)
International Financial Reporting Standards, commonly known as IFRSs, are uniform accounting standards issued by the International Accounting Standards Board (IASB) in 2001. The Saudi Organization for Certified Public Accountants (SOCPA) from 1st Jan 2016 has announced its decision to converge their National Accounting Standard with IFRS. The standards will surely be going to influence the financial system of the country. Every country has its own Generally Accepted Accounting Principles (GAAP). However, an understanding is needed to evaluate the adoption and awareness of IFRS among students and academicians in Saudi Arabia. The present study attempted to examine the awareness and interest of students concerning IFRS. This study has brought some hard facts regarding IFRS convergence in Saudi Arabia. The IFRS will only be able to yield fruitful results when all stakeholders are fully aware, interested, taken into confidence, and ready to cooperate with the directives of the Saudi Organization for Certified Public Accountants (SOCPA) for IFRS adaption.